Read my lips? Taxes and elections - Clemens Fuest; Klaus Gründler; Niklas Potrafke; Fabian Ruthardt (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2022)
Research on many important questions on taxation is impeded by a lack of cross-nationally comparable data. We introduce a new dataset that includes quantitative harmonized indices of tax reforms based on qualitative information of about 900 Economic Surveys from the OECD and 37,000 tax-related news from the IBFD archives collected by the IMF (Amaglobeli et al., 2018). Our dataset provides indicators on tax reforms for tax rates and tax bases, along with detailed sub-indices for six types of taxes (23 countries, 1960-2014). Relating tax reforms to the timing of elections, we provide first empirical evidence on electoral cycles in tax reforms on the national level. Our results show that politicians postpone tax rate increases to after elections. Examining heterogeneity across tax types, we find that electoral cycles are particularly pronounced for value added tax rates and personal income tax rates.
Keywords: D72; H20; H25; C23; 330; Tax reforms; tax systems; tax rates; tax bases; data set; electoral cycles